2007
DOI: 10.1002/cbic.200600449
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Plasmon‐Resonance‐Based Chemical Proteomics: Efficient Specific Extraction and Semiquantitative Identification of Cyclic Nucleotide‐Binding Proteins from Cellular Lysates by Using a Combination of Surface Plasmon Resonance, Sequential Elution and Liquid Chromatography–Tandem Mass Spectrometry

Abstract: Chemical proteomics is a powerful methodology for identifying the cellular targets of small molecules, however, it is biased towards abundant proteins. Therefore, quantitative strategies are needed to distinguish between specific and nonspecific interactions. Here, we explore the potential of the combination of surface plasmon resonance (SPR) coupled to liquid chromatography-tandem mass spectrometry (LC-MS/MS) as an alternative approach in chemical proteomics. We coupled cGMP molecules to the SPR chip, and mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…A 14-3-3 protein could be identified after passing a cauliflower extract over the sensorchip followed by elution, tryptic digestion, MALDI-TOF MS and database searching (19). Other studies have identified proteins eluted from the Biacore sensorchip by reversed phase high-performance liquid chromatography coupled to electrospray ionization tandem mass spectrometers (LC-ESI MS/MS) (20)(21)(22).…”
Section: Spr/msmentioning
confidence: 99%
“…A 14-3-3 protein could be identified after passing a cauliflower extract over the sensorchip followed by elution, tryptic digestion, MALDI-TOF MS and database searching (19). Other studies have identified proteins eluted from the Biacore sensorchip by reversed phase high-performance liquid chromatography coupled to electrospray ionization tandem mass spectrometers (LC-ESI MS/MS) (20)(21)(22).…”
Section: Spr/msmentioning
confidence: 99%
“…Srt.a488 DAPI anti-mouse approach for interaction analysis of certain proteins has been recently developed by combining SPR based biomolecular interaction (BIA) with mass spectrometry (MS), termed BIA/MS, to analyze protein-protein complexes present in cell lysates with a faster way and with less sample requirements compared to the conventional techniques [25][26][27][28][29][30][31]. The BIA/MS method also requires the application of a capturing molecule which forms a stable complex with the target protein(s) and this generally makes possible the isolation of the molecular components additionally bound to the target molecule, too.…”
Section: Biotin-mc-lr Merge Pp1cmentioning
confidence: 99%
“…Coupling of biomolecular interaction analysis (BIA) with mass spectrometry (MS) termed as BIA/MS approaches [26,27] might lead to the design and development of SPR/MS arrays [28]. The BIA/MS method has been successfully applied for the analysis of binding partners for specific proteins using activator molecules [29], multi-affinity antibody surfaces [26], epitope-tagged [30] or GST-fusion proteins [31] as capture molecules. Some SPR equipment allows to increase the binding surface of the sensorchip by using an external unit in which the interaction analysis could be carried out on the whole chip surface [31].…”
Section: Introductionmentioning
confidence: 99%
“…Elution of the surface bound ligand, collecting the sample for further handling and MS analysis has been described as well. This strategy is by now the most popular implementation for studies in which SPR is successfully combined with MS (Bouffartigues et al, 2007;Lopez et al, 2003;Sönksen et al, 1998;Visser et al, 2007). In the combinations of SPR and MS, MALDI-ToF is the most often used method for MS analysis as it is both sensitive and accurate, and is relatively forgiving for minor contaminants present in a sample like salt residues originating from the various non-volatile buffers used in SPR (Nedelkov and Nelson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the combinations of SPR and MS, MALDI-ToF is the most often used method for MS analysis as it is both sensitive and accurate, and is relatively forgiving for minor contaminants present in a sample like salt residues originating from the various non-volatile buffers used in SPR (Nedelkov and Nelson, 2000). Alternatively, Liquid Chromatography coupled with Electrospray Ionisation-MS (LC-ESI-MS), a system often used in proteomics research, has been increasingly employed in combination with SPR (Hayano et al, 2008;Marchesini et al, 2008;Natsume et al, 2000;Visser et al, 2007).…”
Section: Introductionmentioning
confidence: 99%